Linking emotional intelligence to mathematical critical thinking performance among high school students - Lilis Saputri; Adinda Thaibah; Depa Mustika (Institute of Information Technology and Social Science (IITSS), 2025)
This study investigates the relationship between emotional intelligence and students’ mathematical critical thinking using a quantitative ex-post facto design. The sample consisted of 29 Grade XI Science students from SMA Negeri 1 Binjai District, Langkat Regency, selected through purposive sampling. Data were collected using two instruments: a mathematical critical thinking test and an emotional intelligence questionnaire. The Spearman correlation test indicated a coefficient of -0.127 with a significance value of 0.512, exceeding the 0.05 threshold. These results demonstrate that emotional intelligence does not have a significant correlation with mathematical critical thinking skills. Contrary to many previous studies that reported a positive association between emotional intelligence and higher-order cognitive abilities, this research presents a divergent finding. The lack of association suggests that emotional intelligence may not directly contribute to critical thinking in mathematical problem-solving, particularly within instructional environments that rely heavily on teacher-centered approaches. This outcome implies that cognitive enhancement in mathematics may depend more on external academic stimuli than on students’ affective attributes. Future research is recommended to examine potential mediating variables, such as academic motivation, classroom engagement, peer interaction, or instructional design. Understanding these indirect pathways may provide a more comprehensive explanation of how emotional intelligence interacts with cognitive performance.